Workload assessment of medical doctors at primary health care centers in the Duhok governorate - Samim Ahmed Al-Dabbagh; Hushyar Musa Sulaiman; Nazik Abdulrahman Abdulkarim (BMC, 2022)
Abstract Background A shortage in human resources, particularly physicians, has become a challenge confronting health authorities in the Duhok governorate, as these resources are the key input for delivering health care. It has become necessary to identify the most appropriate scientifically sound method for having adequate staffing levels. This study aimed to forecast the required number of physicians to cope with the current workload at the main primary health care centers in the Duhok governorate. Methods A cross-sectional study was adopted to collect data for 1 full year. Data collection included both primary and secondary data sources. A semi-structured questionnaire was developed to obtain information every month from health centers on activities related to training and leaves. Data analysis was performed using Workload Indicators of Staffing Need software. Results Sixty-one primary health care centers met the final criteria for analysis. The study revealed physician shortages and inequity in the distribution of staffing. In these centers, 145 physicians lacked an adequate delivery of health services based on the workload imposed on them. The 'workload indicators of staffing need' ratio was 0.33, indicating high work pressure on medical doctors. Some centers offered more health care than others, but had fewer doctors based on the current staffing practices. Conclusions This study pointed out the importance for the public health sector and academic medical institutions to use Workload Indicators of Staffing Needs software in health policy administration to restructure their efforts to address the physician shortages and distribution imbalances at primary health care facilities.